Does participation benefit children’s socio-emotional development? Positive associations between children’s participation and self-concept, through children’s perceptions - Correia, N.; Carvalho, H.; Aguiar, C. (Early Education and Development, 2024)
Participation, a fundamental right of all children, is described as an indicator of early childhood education (ECE) settings’ quality, and as an investment in children’s development and well-being. Teachers and children influence each other, within interactions that shape participatory processes. In this study, we examined associations between ECE teachers’ participation practices (i.e. both self-reported and observed), observed teacher-child interactions, and children’s socio-emotional outcomes (i.e. self-concept and social skills), mediated by children’s perceptions of their own participation. Participants in this study were 336 children (163 boys), aged between 42 and 76 months (M = 60.14, SD = 7.86), from 58 ECE classrooms in the Lisbon area, Portugal, and their lead teachers. Research Findings: Suggest positive associations between observed participation practices and children’s self-concept, mediated by children’s perceptions of participation. To our knowledge, this study represents the first empirical attempt to address the mechanisms by which participation practices are associated with children’s developmental outcomes, valuing children’s subjective experiences of participation, and accounting for different informants and levels of analysis. Practice or Policy: The main findings and study implications for research, practice, and policymaking are discussed.